2020
DOI: 10.1002/jcsm.12613
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a description of sarcopenic obesity defined as excess adiposity and low lean mass relative to adiposity

Abstract: Background This study aims to assess the construct validity of a body composition-defined definition of sarcopenic obesity based on low appendicular lean mass relative to fat mass (ALMI FMI) and high fat mass index (FMI) and to compare with an alternative definition using appendicular lean mass index (ALMI) and percent body fat (%BF). Methods This is a secondary analysis of two cohort studies: the National Health and Examination Survey (NHANES) and the Health, Aging, and Body Composition study (Health ABC). Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
1
15
1
Order By: Relevance
“…Therefore, estimates using BMI rather than percentage BF may underestimate the prevalence of OLLMM, with greater disparity observed in older populations. Compared with previous prevalence estimates using NHANES data from prior survey years in those aged 20–59 years (ranged from 3.3–5.5% [ 27 , 29 ]) and ≥ 60 years (ranged from 7.0–27.3% [ 28 , 29 , 41 ]), our estimates were generally higher [ 27 29 ]. This may be due to an increase in the overall prevalence of disease, variability in the definition, or greater sensitivity of the methodology used in this analysis.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Therefore, estimates using BMI rather than percentage BF may underestimate the prevalence of OLLMM, with greater disparity observed in older populations. Compared with previous prevalence estimates using NHANES data from prior survey years in those aged 20–59 years (ranged from 3.3–5.5% [ 27 , 29 ]) and ≥ 60 years (ranged from 7.0–27.3% [ 28 , 29 , 41 ]), our estimates were generally higher [ 27 29 ]. This may be due to an increase in the overall prevalence of disease, variability in the definition, or greater sensitivity of the methodology used in this analysis.…”
Section: Discussioncontrasting
confidence: 73%
“…Previous prevalence estimates of sarcopenic obesity in the USA, obtained from National Health and Nutrition Examination Survey (NHANES) data, are limited. Several of the prior estimates rely on data roughly 20 years old [27][28][29]. Additionally, the estimate using more recent data (NHANES 2017-2018) does not include participants aged > 59 years, thus excluding the population at the highest risk for sarcopenic obesity [30].…”
Section: Introductionmentioning
confidence: 99%
“…Five studies combined the criteria including BF% or BMI to diagnose obesity 30 . Another three studies used total fat mass, 47 high triglyceride and WC (as indicator of visceral obesity), 48 and fat mass index to diagnose obesity 44 . Among 10 studies that reported mortality data, five utilized muscle index adjusted by ht 2 with or without functional tests to diagnose sarcopenia, and six of them used BF% to identify obesity.…”
Section: Resultsmentioning
confidence: 99%
“…Among the analyzed studies, three used handgrip strength to identify sarcopenia. [38][39][40] Five used predicted muscle mass area, 41 urine creatine, 42 muscle cross-sectional area (CSA) adjusted by weight, 43 ASM adjusted by fat mass, 44 and midarm muscle circumference to diagnose sarcopenia. 45 In addition, 80 studies reported definitions of obesity.…”
Section: Definitions Of Sarcopenic Obesitymentioning
confidence: 99%
“…The construction of the FM/FFM ratio integrated the metabolic effect of both fat mass and fat-free mass. This indicator was regarded as a measurement of sarcopenic obesity, a body composition-defined definition using to describe individuals with both evidence of muscle loss and excess adiposity [ 17 , 32 ]. It has been reported that individuals had the highest risk when there was a concurrence of sarcopenia and obesity [ 30 ].…”
Section: Discussionmentioning
confidence: 99%